2022
DOI: 10.3390/ijerph191811316
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Course of Depression and Anxiety after COVID-19 Infection between Recovered Patients with and without a Psychiatric History: A Cross-Sectional Study

Abstract: Background: This study aimed to examine the course of depression and anxiety in COVID-19 survivors with a psychiatric history compared with those without a psychiatric history. Methods: A web-based cross-sectional survey for COVID-19 survivors was conducted from July to September 2021. A total of 6016 COVID-19 survivors, the accuracy of whose responses was determined to be assured, were included in analyses. Exposures included psychiatric history and time since COVID-19 infection, and the main outcomes and mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
(74 reference statements)
1
14
0
Order By: Relevance
“…Physical comorbidity was associated with depression and anxiety, as a systematic review indicates that any comorbidity before COVID-19 infection was related to depression and anxiety (17); some studies also suggest that the baseline Charlson comorbidities index predicts depression and anxiety after infection (18,19). In addition, the relationship between a psychiatric history and depression and anxiety was also reported by previous studies (19,21,75). As for the duration after infection, depression remained over time except at the 6-month time point, and anxiety was higher at over one month than at less than one month.…”
Section: Participant Characteristicsmentioning
confidence: 57%
“…Physical comorbidity was associated with depression and anxiety, as a systematic review indicates that any comorbidity before COVID-19 infection was related to depression and anxiety (17); some studies also suggest that the baseline Charlson comorbidities index predicts depression and anxiety after infection (18,19). In addition, the relationship between a psychiatric history and depression and anxiety was also reported by previous studies (19,21,75). As for the duration after infection, depression remained over time except at the 6-month time point, and anxiety was higher at over one month than at less than one month.…”
Section: Participant Characteristicsmentioning
confidence: 57%
“…Therefore, confirming the association between preexisting psychiatric disorders and post-COVID-19 among people who would not have used medical care after recovering from COVID-19 infection is necessary. Our previous study showed that the courses of depressive and anxiety symptoms after the infection of COVID-19 were more severe in COVID-19 survivors with preexisting psychiatric disorders than in those without the disorders 15 . However, the association between preexisting psychiatric disorders and physical symptoms of post-COVID-19 is still unknown.…”
Section: Introductionmentioning
confidence: 93%
“…A bidirectional relationship between COVID-19 and psychiatric diseases has been suggested, with SARS-CoV-2 infection predisposing to subsequent psychiatric symptoms and previous diagnoses of mental illness being a risk factor for worse COVID-19 outcomes, higher mortality rates, and long-term residual symptoms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence described the association between mood disorders and immune-inflammatory activation manifested through increased levels of inflammatory indexes [ 13 ], and inflammatory processes have been, to some extent, correlated with recurrence of episodes [ 14 16 ]. Thus, according to the involvement of neuroinflammation in the pathophysiology of mental illnesses, it has been proposed that a psychiatric history could further promote inflammation during and after SARS-CoV-2 infection and result in more severe depressive and anxious symptoms and a greater unlikelihood of recovery in the short time [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation